Pengaruh Struktur Modal, Likuditas Dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Otomotif Yang Terdaftar Di BEI Tahun 2018 - 2022 - Akmal Mufid; Indrayeni (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to examine the influence of capital structure, liquidity and company size on company profitability. The population used in this research is all automotive sub-sector companies listed on the Indonesian stock exchange for the 2018-2022 period. The number of samples in this study was 59 samples. This research uses a quantitative approach. The data analysis technique used is multiple linear analysis which was processed using the SPSS 21 program. The results of this research show that capital structure has a negative and significant effect on company profitability. Liquidity does not have a significant effect on company profitability and company size does not have a significant effect on company profitability. Simultaneously, capital structure, liquidity and company size influence the profitability of automotive sub-sector companies listed on the Indonesian stock exchange for the 2018-2022 period. It is hoped that the results of this research can be used by interested parties such as companies in taking preventive measures to avoid bankruptcy as well as investors in making decisions on investments invested.